Geochemical relations of In (Indium) bearing Sphalerite in the San Roque Project (Río Negro Province, Argentina) - González, María Violeta (2022)
Indium (In) is a metal used in high technology especially in semiconductors and liquid crystal displays (Nauckhoff von 2011). They have been reported until now few indium discoveries in Argentina: in Patagonian epithermal deposits as Pingüino, La Luz, Toruel and San Roque projects, Gonzalito and Angela mines (Jovic et al. 2015) and El Peladar in Jujuy province (Zappettini et al. 2004). The San Roque property is located within Valcheta and San Antonio Oeste departments, Río Negro province, covering an area of 11.381,5 hectares. Mineralization is located in galena, pyrite, chalcopyrite, sphalerite, quartz and carbonates. Mineralization occurs as zones of narrow, sheeted quartz-carbonate-sulphide veins and stockworks as well as sulphide disseminations within host Jurassic volcanic and volcaniclastic rocks.